2014
DOI: 10.1002/2013jc009635
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency ocean bottom pressure variations in the North Pacific in response to time‐variable surface winds

Abstract: One decade of time-variable gravity field observations from the GRACE satellite mission reveals low-frequency ocean bottom pressure (OBP) variability of up to 2.5 hPa centered at the northern flank of the subtropical gyre in the North Pacific. From a 145 year-long simulation with a coupled chemistry climate model, OBP variability is found to be related to the prevailing atmospheric sea-level pressure and surface wind conditions in the larger North Pacific area. The dominating atmospheric pressure patterns obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Similarly, the Atlantic Multidecadal Oscillation (AMO), has been reported to have nearly global influences on the climate system (e.g., Knight et al 2006), including Amazonian (e.g., Kayano et al 2016) or Sahelian (e.g., Mohino et al 2011) rainfall, Atlantic hurricanes (e.g., Zhang and Delworth 2006), North American (e.g., Hu et al 2011) and European summer climate (e.g., Zampieri et al 2017). More and more frequently, it is found that a single climate mode is not sufficient to explain the major characteristics of regional climates, but that a combination of several modes, interacting with one another, is necessary to gain in climate predictability (e.g., Morrow et al 2010;Li and Wettstein 2012;Kayano and Capistrano 2014;Petrick et al 2014;Kundzewicz et al 2019). Besides, it has been suggested that climate modes may not be stationary and that the spatial and temporal characteristics of climate modes, as well as their relationships with one another, may be evolving in a changing climate (e.g., Litzow et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the Atlantic Multidecadal Oscillation (AMO), has been reported to have nearly global influences on the climate system (e.g., Knight et al 2006), including Amazonian (e.g., Kayano et al 2016) or Sahelian (e.g., Mohino et al 2011) rainfall, Atlantic hurricanes (e.g., Zhang and Delworth 2006), North American (e.g., Hu et al 2011) and European summer climate (e.g., Zampieri et al 2017). More and more frequently, it is found that a single climate mode is not sufficient to explain the major characteristics of regional climates, but that a combination of several modes, interacting with one another, is necessary to gain in climate predictability (e.g., Morrow et al 2010;Li and Wettstein 2012;Kayano and Capistrano 2014;Petrick et al 2014;Kundzewicz et al 2019). Besides, it has been suggested that climate modes may not be stationary and that the spatial and temporal characteristics of climate modes, as well as their relationships with one another, may be evolving in a changing climate (e.g., Litzow et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While redistributions of mass between ocean basins reflect dynamic changes in ocean circulation, for example, caused by wind stress anomalies (Boening et al, ; Petrick et al, ), changes in total ocean mass are predominantly related to imbalances in the net freshwater flux from land and atmosphere, that is, ocean evaporation, precipitation, global ice discharge, and river runoff. In principle, three methods exist for deriving ocean mass change: (1) Altimetric observation of the total sea level change is corrected for steric (i.e., volumetric) sea level change from in situ observations of temperature and salinity profiles and from modeling; (2) mass changes are directly obtained from Gravity Recovery and Climate Experiment (GRACE) satellite data products (e.g., Johnson & Chambers, ); (3) GRACE mass observation and altimetric sea level observation are combined in an inverse approach (Rietbroek et al, ) where one jointly solves for mass change and steric variations.…”
Section: Introductionmentioning
confidence: 99%
“…In situ observations of OBP (e.g., Ito et al 2013) have occurred in only recent history, such that wide-area annual variation patterns have not been adequately revealed. On the other hand, a regional-scale OBP was revealed by a satellite gravity mission (e.g., Petrick et al 2014). Assimilating observations with such different space-time resolutions will be key toward improving the ocean model.…”
Section: Discussionmentioning
confidence: 99%